An orbital-overlap model for minimal work functions of cesiated metal surfaces - Chou, Sharon H; Voss, Johannes; Bargatin, Igor; Vojvodic, Aleksandra; Howe, Roger T; Abild-Pedersen, Frank (Journal of physics. Condensed matter, 2012)
We introduce a model for the effect of cesium adsorbates on the work function of transition metal surfaces. The model builds on the classical point-dipole equation by adding exponential terms that characterize the degree of orbital overlap between the 6s states of neighboring cesium adsorbates and its effect on the strength and orientation of electric dipoles along the adsorbate-substrate interface. The new model improves upon earlier models in terms of agreement with the work function-coverage curves obtained via first-principles calculations based on density functional theory. All the cesiated metal surfaces have optimal coverages between 0.6 and 0.8 monolayers, in accordance with experimental data. Of all the cesiated metal surfaces that we have considered, tungsten has the lowest minimum work function, also in accordance with experiments.